2017
DOI: 10.3346/jkms.2017.32.1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pharmacomechanical Endovascular Intervention for Iliofemoral Vein Thrombosis Compared to Conventional Anticoagulation Therapy

Abstract: Although anticoagulation therapy is the primary treatment for deep vein thrombosis (DVT), it has not been associated with the rapid recanalization of the venous occlusion. Moreover, it is associated with long-term disability due to post-thrombotic syndrome (PTS). In contrast, pharmacomechanical endovascular intervention (PMI) results in more rapid clinical improvement in DVT patients, but there are few reports on its long-term outcomes. This retrospective study evaluated the clinical effectiveness of PMI compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Ulcers were reported in 7 (5.5%) medically treated vs 5 interventionally treated patients (5%) vs 7 (5.5%). 16,18,19 Venous disability score and clinical score was reported in the study by Plate et al as shown in Table 3.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Ulcers were reported in 7 (5.5%) medically treated vs 5 interventionally treated patients (5%) vs 7 (5.5%). 16,18,19 Venous disability score and clinical score was reported in the study by Plate et al as shown in Table 3.…”
Section: Resultsmentioning
confidence: 98%
“…There were 233 eligible studies that were evaluated as full-text articles. After full-text assessment, 8 studies 1219 were included in this systematic review. The flow diagram is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the thrombus removal rate and recurrence free rate, we did not find any significant differences of clinical importance between the CDT and ACA groups; however, evidence of more adverse events was noted in the CDT group. Although there were no deaths during hospitalization, four patients had active bleeding that required transfusion and bleeding control after CDT [1,24].…”
Section: Discussionmentioning
confidence: 99%
“…9,28 Additional long-term follow-up data were provided by observational analyses with a low level of evidence for which the exact period of surveillance was difficult to define and the application of objective tools in the assessment of symptoms was questioned. 9,[29][30][31] The low rate of CDT technical success in the CAVA trial resulted in further arguments regarding the need and usefulness of these comparative studies between CDT and anticoagulation therapy alone. The CAVA trial failed to prove that ultrasound-assisted thrombolysis is superior to CDT alone.…”
Section: Limitations Of Currently Available Rctsmentioning
confidence: 99%